Understanding the Population Structure of North American Patients with Cystic Fibrosis - Li, Weili (2011)
RATIONALE: It is generally presumed that the Cystic Fibrosis (CF) population is relatively homogeneous, and predominantly of European origin. The complex ethnic make-up observed in the CF patients collected by the North American CF Modifier Gene Consortium has brought this assumption into question, and suggested the potential for population substructure in the three CF study samples collected from North America. It is well appreciated that population substructure can result in spurious genetic associations. OBJECTIVES: To understand the ethnic composition of the North American CF population, and to assess the need for population structure adjustment in genetic association studies with North American CF patients. METHODS: Genome-wide single-nucleotide polymorphisms on 3076 unrelated North American CF patients were used to perform population structure analyses. We compared self-reported ethnicity to genotype-inferred ancestry, and also examined whether geographic distribution and CFTR mutation type could explain the structure observed. MAIN RESULTS: Although largely Caucasian, our analyses identified a considerable number of CF patients with admixed African-Caucasian, Mexican-Caucasian and Indian-Caucasian ancestries. Population substructure was present and comparable across the three studies of the consortium. Neither geographic distribution nor mutation type explained the population structure. CONCLUSION: Given the ethnic diversity of the North American CF population, it is essential to carefully detect, estimate and adjust for population substructure to guard against potential spurious findings in CF genetic association studies. Other Mendelian diseases that are presumed to predominantly affect single ethnic groups may also benefit from careful analysis of population structure.